In Vitro Inhibition Effect and Molecular Docking Study of Curcumin, Resveratrol, and Quercetin on Human Erythrocyte Glutathione Transferase - Aksoy, Mine; Karaman, Muhammet; Güller, Pınar; Güller, Uğur; Küfrevioğlu, Ö. İrfan (Current Enzyme Inhibition, 2019)
Background: Chemotherapy has shown varying success rates in the treatment of metastatic cancer in the last 50 years. One of the problems in the use of many chemotherapeutic agents is to increase the expression of glutathione transferase enzyme (GST; EC 2.5.1.18). Therefore, the development of GST inhibitors is important to improve the effectiveness of antitumor drugs and to overcome multi-drug resistance. Introduction: Glutathione S-transferases (GSTs) are a major member of enzymes serving in the detoxification of exogenous and endogenous substances. But, it has been reported that GSTs are overexpressed in many tumour cells, and it has been found to be related to developing resistance to anticancer drugs by these cells. The development of GST inhibitors is important to increase the efficacy of antitumor drugs and overcome multi-drug resistance. The aim of our study was to investigate the effect of natural compounds including curcumin, resveratrol, and quercetin on GST enzyme activity. We also aimed to specify inhibition mechanism of the compounds on human erythrocytes GST (hGST) with in silico study. Methods: GST was purified from human erythrocytes using affinity chromatography (glutathione agarose). The enzyme purity was checked with SDS-PAGE. After the inhibitory effect of the curcumin, quercetin, resveratrol was investigated. Lastly, inhibition mechanisms of these natural compound were identified with induced-fit docking method. Results: GST was purified with 19.31% yield from human erythrocytes. In inhibition studies, Ki values of curcumin, quercetin, resveratrol were determined as 0.0021 ± 0.0008, 0.0257 ± 0.0011, 663.3301 ± 0.0936 μM respectively. According to our results, all natural products showed the inhibition effect and the order of inhibition is as follows: curcumin > quercetin > resveratrol. Conclusion: According to the results of the in vitro and in silico studies, it can be said that curcumin, quercetin, resveratrol are the inhibitors of human erythrocyte GST. In conclusion, these observations may be of great importance for the potential use of these natural compounds as chemopreventive agents.
Keywords: in silico study